A new Cu2+-selective fluorescent probe with six-membered spirocyclic hydrazide and its application in cell imaging. (December 2019) - Huang, Kun; Han, Defang; Li, Xianglin; Peng, Mengni; Zeng, Xianshun; Jing, Linhai; Qin, Dabin
Abstract: A new N-heterocyclic fluoran based dyeBiF is facilely prepared in high yield by reaction of 5-methoxybenzimidazole and 2-(4-diethylamino-2-hydroxy)benzoylbenzoic acid in concentrated H2 SO4, which keeps stable optical signals in water at pH values ranging from 4 to 10 and exhibits good living cell membrane permeability. By modification of the spirolactone in moleculeBiF, a fluorescent probeBiF–Cu with specific and sensitive response to Cu 2+ has been further developed, which contains a six-membered spirolic hydroxyethylhydrazide moiety that can be selectively triggered by Cu 2+ among various metal ions through a specific cascade reaction of Cu 2+ -promoted spirolactam ring-opening and hydrolysis. A limit of detection for Cu 2+ is calculated as 7.12 × 10 −8  mol/L. In addition, the utilization ofBiF–Cu for bioimaging Cu 2+ in L929 cells demonstrates its living cell membrane permeability and makes it promising candidate for monitoring Cu 2+ by cell imaging technology. Graphical abstract: A new N-heterocyclic fluoranBiF has been efficiently prepared by hybridizing benzimidazole and fluoran moieties. Based on this dye, fluorescent probeBiF–Cu with unique six-membered spirocyclic hydrazide has been developed for selective and sensitive detection of Cu 2+ and cell imaging.Image 1 Highlights: A new N -heterocyclic fluoran dye was prepared with stable optical signal over a wide pH range. A fluorescent probe containing a novel six-membered spirocyclic hydrazide trigger has been developed. The probe was empolyed for highly selective and sensitive detection of Cu 2+ with a detection limit of 71.2 nM. The probe can be utilized in tracing Cu 2+ in living cell.